An integrative taxonomic approach reveals two putatively novel species of phlebotomine sand fly (Diptera: Psychodidae) in Thailand - Samiullah Soomro; Siwaporn Tuangpermsub; Thongchai Ngamprasertwong; Morakot Kaewthamasorn (Parasites & Vectors, 2025)
Abstract Background The subfamily Phlebotominae comprises 1028 species of sand fly, of which only 90 are recognized as vectors of pathogenic agents such as Trypanosoma, Leishmania, and Bartonella. In Thailand, leishmaniasis—a sand fly-borne disease—is currently endemic, with 36 documented sand fly species. However, many cryptic species likely remain unidentified. To improve our understanding of the distribution, habitat preferences, and role in disease transmission of these sand flies, further research is necessary. Methods Sand flies were collected using CDC light traps from 13 locations across four provinces in Thailand between October 2022 and October 2023. Initially, species identification was based on morphological characteristics, employing identification keys, and subsequently confirmed through mitochondrial cytochrome oxidase c subunit I (COI) and cytochrome b (Cytb) sequencing. Species identities were verified using BLASTN and BOLD searches. Species delimitation was conducted using Automatic Barcode Gap Discovery (ABGD) and Assemble Species by Automatic Partitioning (ASAP) with three substitution models. Additionally, intraspecific and interspecific genetic variation, neutrality tests (including Tajima’s and Fu and Li’s D* tests), phylogenetic analyses, and TCS haplotype network analysis were performed using the obtained sequences. Results A total of 3693 phlebotomine sand flies were collected, with 2261 (61.22%) identified as female. Integrative analyses combining morphological data, BLASTN searches, phylogenetic assessments, and species delimitation confirmed the identification of four genera: Sergentomyia, Grassomyia, Phlebotomus, and Idiophlebotomus, encompassing 12 species: Sergentomyia anodontis, Se. sylvatica, Se. perturbans, Se. barraudi, Se. hivernus, Se. khawi, Se. siamensis, Grassomyia indica, Phlebotomus barguesae, Ph. stantoni, Idiophlebotomus asperulus, and Id. longiforceps. Furthermore, molecular analysis revealed cryptic and complex species, including two putatively novel species, Se. sp. 1 and Se. sp. 2, as well as a unique haplotype. Conclusions This study, which integrated genetic and morphological identification techniques, identified 12 sand fly species and unveiled cryptic and complex species, including two putatively novel species (Se. sp. 1 and Se. sp. 2) and a unique haplotype. The findings underscore the utility of mitochondrial genes, combined with species delimitation methodologies, as reliable approaches for identifying diverse sand fly species. Graphical Abstract